Urinary tract infection and febrile seizure Is there any association? - Mahyar, Abolfazl; Ayazi, Parviz; Azimi, Elaheh; Dalirani, Reza; Ameneh Barikani, Ameneh Barikani; Esmaeily, Shiva (Iranian Journal of Child Neurology, 2018)
Background: Febrile seizure is the most common type of seizure among children. Identification of factors involved in febrile seizure is highly critical. Purpose: The present study was conducted to determine the association between children’s urinary tract infection and febrile seizure. Materials and Methods: In this case-control study, 165 children with simple febrile seizure (case group) were compared with 165 children with fever and without seizure (control group) in terms of urinary tract infection. The age of children was between 6 months to 5 years. The results of both groups were analyzed and compared. Results: Among 165 children with febrile seizure, 25 subjects (15.2%) had urinary tract infection. In the control group, only 2 patients (1.2%) had UTI. There was significant difference between two groups regarding urinary tract infection (P=0.001). Among 25 children with UTI in the case group, 17 children (68%) had acute pyelonephritis, and the remaining 8 children (32%) had cystitis. The two patients with UTI in control group had cystitis (P=0.055). Conclusion: The present study showed that urinary tract infection could be a risk factor of febrile seizure. Therefore, it is recommended that all patients with febrile seizure be examined in terms of urinary tract infection.